An increase in precipitation exacerbates negative effects of nitrogen deposition on soil cations and soil microbial communities in a temperate forest. (April 2018) - Shi, Leilei; Zhang, Hongzhi; Liu, Tao; Mao, Peng; Zhang, Weixin; Shao, Yuanhu; Fu, Shenglei
Abstract: World soils are subjected to a number of anthropogenic global change factors. Although many previous studies contributed to understand how single global change factors affect soil properties, there have been few studies aimed at understanding how two naturally co-occurring global change drivers, nitrogen (N) deposition and increased precipitation, affect critical soil properties. In addition, most atmospheric N deposition and precipitation increase studies have been simulated by directly adding N solution or water to the forest floor, and thus largely neglect some key canopy processes in natural conditions. These previous studies, therefore, may not realistically simulate natural atmospheric N deposition and precipitation increase in forest ecosystems. In a field experiment, we used novel canopy applications to investigate the effects of N deposition, increased precipitation, and their combination on soil chemical properties and the microbial community in a temperate deciduous forest. We found that both soil chemistry and microorganisms were sensitive to these global change factors, especially when they were simultaneously applied. These effects were evident within 2 years of treatment initiation. Canopy N deposition immediately accelerated soil acidification, base cation depletion, and toxic metal accumulation. Although increased precipitation only promoted base cation leaching, this exacerbated the effects of N deposition. Increased precipitation decreased soil fungal biomass, possible due to wetting/re-drying stress or to the depletion of Na. When N deposition and increased precipitation occurred together, soil gram-negative bacteria decreased significantly, and the community structure of soil bacteria was altered. The reduction of gram-negative bacterial biomass was closely linked to the accumulation of the toxic metals Al and Fe. These results suggested that short-term responses in soil cations following N deposition and increased precipitation could change microbial biomass and community structure. Graphical abstract: Image 1 Highlights: Negative effects of N on soil cations could be exacerbated with precipitation. Increased precipitation immediately decreased soil fungal biomass. Combined N and rainfall reduced soil G − bacterial biomass. Combined N and rainfall immediately altered soil bacterial community structure. Reduction of G − bacterial biomass was linked to the accumulation of toxic metals. Abstract : The negative effects of canopy N deposition on soil acidification, base cation depletion, and toxic metal accumulation were exacerbated with precipitation increase.